The Revival Movement of the Idrisiyya Order in Indonesia - Sulaiman, Sulaiman; Ula, Miftahul; Faiq, Muhammad; Machrus, Machrus; Yusriyah, Yusriyah; Ulfah, Rokhmah (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
Sufism and ṭarīqa are often associated with awful and negative stigmas for generating laziness, stagnancy, and surrender to misery. Sheikh Fathurahman tackles these assumptions through the teachings of the Idrisiyya Order. This study is qualitative based research. The primary data were collected from books by Sheikh Fathurahman and his lectures uploaded on Youtube, observations, Focus Group Discussions, and direct and indirect interviews. This study found that Sufi revivalism, as initiated by Sheikh Fathurahman, has led to a positive movement. The presence of the ṭarīqa, especially the Idrisiyya Order, amid society has contributed to crucial social changes and innovations in some sectors, such as economics, education, and other social programs. Contribution: This study will give a new insight into the central teaching of taṣawwuf, such as zuhd and tawakkal as reinterpreted by Sheikh Fathurahman under the Idrisiyya Order so that ṭarīqa becomes the locomotive of social change amid Muslim society in Indonesia.